The Human Upper Respiratory Tract Epithelium Is Susceptible to Flaviviruses - Vielle, Nathalie J.; García-Nicolás, Obdulio; Oliveira Esteves, Blandina I.; Brügger, Melanie; Summerfield, Artur; Alves, Marco P. (Frontiers in Microbiology, 2019)
Flaviviruses replicate in a wide variety of species and have a broad cellular tropism. They are isolated from various body fluids and Zika virus (ZIKV), Japanese encephalitis virus (JEV) and West Nile virus (WNV) RNAs have been detected in nasopharyngeal swabs. Consequently, we evaluated the cellular tropism and host responses upon ZIKV, JEV, WNV, and Usutu virus (USUV) infection using a relevant model of the human upper respiratory tract epithelium based on primary human nasal epithelial cells (NECs) cultured at the air-liquid interface. NECs were susceptible to all the viruses tested and confocal analysis showed evidence of infection of ciliated and non-ciliated cells. Each flavivirus productively infected NECs, leading to apical and basolateral live virus shedding with particularly high basal release for JEV and WNV. As demonstrated by a paracellular permeability assay, the integrity of the epithelium was not affected by flavivirus infection suggesting an active release of live virus through the basolateral surface. Also, we detected a significant secretion of interferon type III and the pro-inflammatory cytokine IP-10/CXCL10 upon infection with JEV. Taken together, our data suggest that the human upper respiratory tract epithelium is a target for flaviviruses and could potentially play a role in the spread of infection to other body compartments through basolateral virus release. Undoubtedly, further work is required to evaluate the risks and define the adapted measures to protect individuals exposed to flavivirus-contaminated body fluids.